INDONESIAN STUDENTS LANGUAGE ATTITUDES TOWARDS INDONESIAN AND ENGLISH THROUGH EDUCATION AND WORKING FRAME - Kurniasari, Monika Dini; Mbato, Concilianus Laos (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This research aimed to explore language attitudes of Indonesian EFL learners towards English and Indonesian and studied the relationship of language attitudes in terms of educational background and study programs. A total of 256 Indonesian participants, randomly selected from five universities (two public, three private), answered a two-part questionnaire (Language Background Questionnaire and General Language Attitudes Survey). The analyses of the data expose that the participants alleged to the positive attitudes towards English as they were stimulated to learn the language, and appreciated their English skill as a means to attain better study or work opportunities, meanwhile in view of their native language-Indonesian superior to English. As a result, the study infers that the participants had a positive attitude of Indonesian identity with a positive reception of the importance of the English language. English is significant not only as an international language but also considered as an important language along with Indonesian language in education and profession. This study is a part of a major research project written by a team of researchers from Sanata Dharma University, Yogyakarta Indonesia. The first article investigated relationship the students language attitudes, gender and socio-economic status (ParadewariMbato, 2018). The second article looks into language attitudes and language orientation (Kharismawan Mbato, in press). A similarity will be found across the three articles in terms of data on students language attitudes.